Late Pleistocene and Holocene landscape formation in a gully catchment area in Northern Hesse, Germany. (16th April 2015) - Döhler, Susanne; Damm, Bodo; Terhorst, Birgit; Thiel, Christine; Frechen, Manfred
Abstract: Permanent gully channels under forest are common geomorphological features in Central European low mountain areas. In the Rehgraben/Fuchslöchergraben gully catchment in Northern Hesse, Germany the Late Pleistocene landscape formation is reconstructed based on periglacial cover beds. In addition, the Holocene landscape development and soil erosion history are investigated using anthropogenic soil sediments and alluvial fan sediments. Until now, a combination of these approaches has not been applied to a gully catchment to this extent. The distribution of the different Quaternary sediments enables the differentiation between Pleistocene and Holocene landforms. Radiocarbon and optically stimulated luminescence dating are applied to add numerical data to the relative ages of the sediments and landforms. The gully channels are oriented along Pleistocene depressions that are built up of periglacial cover beds and intercalated reworked loess. As the gully channels cut through the periglacial cover beds, especially the upper layer, the gully system is of Holocene age. At least two phases of gully erosion are identified in the alluvial fan sediments. The initial gully erosion is dated to the time span between the Late Bronze Age and Roman Times. A second gully erosion phase is dated to the 14th century and may be correlated to the severe precipitation events during this time. Gully erosion started during the Younger Holocene and is connected to human settlement and land use activity. The intense human impact hampers the application of the concept of periglacial cover beds to reconstruct landscape formation and limits it to areas where the periglacial upper layer is still preserved.